Farmed fish welfare during slaughter in Italy: survey on stunning and killing methods and indicators of unconsciousness - Clemente, Gianfilippo Alessio; Tolini, Clara; Boscarino, Andrea; Lorenzi, Valentina; Dal Lago, Tania Lidia; Benedetti, Daniele; Bellucci, Fabio; Manfrin, Amedeo; Trocino, Angela; Rota Nodari, Sara (Frontiers in Veterinary Science, 2023)
Information on slaughter procedures for farmed fish in aquaculture is limited, both in Europe and in Italy, due to a general lack of field data. The objective aim of this study was to gather information on the procedures used to slaughter fish in Italy and to discuss them considering the WOAH and EFSA recommendations on fish welfare. Using a questionnaire survey data was collected by official veterinarians in 64 slaughtering facilities where twenty different species of fish were slaughtered. The main species slaughtered were rainbow trout (Oncorhynchus mykiss) (29/64), followed by European sea bass (Dicentrarchus labrax) (21/64), sea bream (Sparus aurata) (21/64), Arctic char (Salvelinus alpinus) (14/64), European eel (Anguilla anguilla) (11/64), sturgeon (Acipenser spp.) (11/64), common carp (Cyprinus carpio) (6/64) and brown trout (Salmo trutta fario L.) (5/64). The most applied stunning/killing methods were "asphyxia in ice /thermal shock" and 'electric in water bath', followed by 'percussion', 'asphyxia in air', and 'electric dry system'. After the application of the method, the assessment of the fish level of unconsciousness was practiced in 720% of the facilities using more than one indicator, with 'breathing' and 'coordinated movements' the most practiced. The collected data showed a discrepancy between the available recommendations about the welfare of fish at slaughter and what is practiced in many production sites, but for many species precise recommendations are still not available.